Stimulation of the internal superior laryngeal nerve as a potential therapy for obstructive sleep apnea in a porcine model - Maurer, Joachim T.; Huseynov, Jamal; Hochreiter, Jakob; Perkins, Justin D. (Journal of applied physiology, 2024)
Download figureDownload PowerPoint
Online veröffentlicht: 18. Juli 2024, Artikelversion: 13. September 2024
Gesehen am 01.04.2025